Impacts of Digital Communication Tools on Fashion Brands Success –The NUDE Project - Peredy, Zoltán; Figueiredo, Carolina; Krisztina, Juhász (International Journal of Engineering and Management Sciences, 2025)
The global scale, changing fashion industry can be characterised with low predictability, high volatility, seasonality, short life cycle products and highly impulse consumer purchasings decisions, addressing ethical and sustainability matters. Fashion as generic collecting name can be defined as styles of clothing and accessories worn at any time by different groups of people. One of the main opportunity and challenge for this complex, multi actors sector introducing digital solutions, which can provide significant contribution of restructuring the supply chains, optimising the production techniques, reducing its negative environmental externalities supporting the future sustainability. Possible reason beyond this digitization trend can be changing consumer attitudes and expectations. Majority of consumers have tendency using digital channels before, during and after their purchase, so fashion brands have to take into consideration this new reality. The convenience and accessibility of online enjoyable shopping opportunities have reshaped consumer expectations including personalized recommendations, and user-friendly online social media platforms (video channels, websites, mobile apps, and secure payment systems). Instagram, TikTok, YouTube and Pinterest have transformed the way fashion brands communicate and connect with their audience creating loyal social network. Digital transformation requires more than just implementing new technologies; it necessitates a cultural shift within fashion brands. Case study of the NUDE Project analysing its challenges and main competitors as well, can serve as an illustrative example how can the digital communication tools contribute to the fashion brand future success and prosperity.